Predicting thermal stress for coral bleaching in the Great Barrier Reef using a coupled ocean–atmosphere seasonal forecast model. (4th April 2012) - Spillman, C. M.; Alves, O.; Hudson, D. A.
Abstract Coral bleaching, triggered by elevated water temperatures, is a serious threat to the future health of the world coral reef systems and represents a considerable challenge for reef management. Seasonal forecast products from coupled ocean–atmosphere models can be used to predict anomalously warm conditions several months in advance and provide early warning of bleaching, allowing for a proactive management response to bleaching. Predictions on a seasonal timescale are the most practical for reef managers, as strategies can be implemented at the start of summer prior to the onset of bleaching. To more accurately assess the potential for bleaching, both duration and magnitude of the thermal stress must be considered, in addition to the probability of an event occurring. In this study, we assess the ability of the Australian Bureau of Meteorology seasonal forecast model (POAMA) to forecast monthly HotSpots and Degree Heating Months in the Great Barrier Reef, Australia, with particular focus on the major 1997/1998 and 2001/2002 bleaching events. Probabilistic forecasts for exceeding certain thresholds are also assessed. This work is part of an ongoing research effort to apply a dynamical seasonal model to the problem of coral bleaching and to provide valuable forecast tools for reef managers at useful time scales. Copyright © 2012 Royal Meteorological Society